ANALISIS PENGUNGKAPAN UNIVERSITY SOCIAL RESPONSIBILITY DI UIN MAULANA MALIK IBRAHIM MALANG - Noval Gibran Lubis; Endang Dwi Wahyuni; Siti Zubaidah (Universitas Muhammadiyah Malang, 2018)
The purpose of this research is to analyze the implementation of green accounting based on university social responsibility UIN Maulana Malik Ibrahim Malang. Respondents in this study were 43 employees at the Maulana Malik Ibrahim State Islamic University Malang. Data acquisition techniques in this study are questionnaires and documentation. This research is descriptive. The results indicate that 1) environmental awareness has a tendency for data with a percentage of 74.00% or in the good category. 2) environmental involvement has tendency of data with percentage 69.09% or mauk in good category. 3) environmental reporting has a 55.58% data trend or is categorized as sufficient. 4) environmental audits also have tendency of data with percentage 59,67% or included in enough category.